Peran Teaching Clinic dalam Proses Pembuatan RPP dan Media Pembelajaran - Mukarromah Mukarromah; Rika Sartika (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2022)
The lesson plan (RPP) and media learning is one of the important component that must be prepared by the candidate teacher before teaching. For university student PPL PAI IAI Darullughah Wadda’wah Bangil that not having teaching’s experience yet, will get the difficulty in creating lesson plan and media learning. Therefore, there is teaching clinic for helping student university of PPL PAI in creating lesson plan and media learning. The kind of research that used is qualitative research by qualitative description. The technique of collecting datas are interview, observation and documentation. Furthermore, the technique of data’s analysis by collecting data, display data and conclusion. The result of teaching clinic has six steps they are workshop of creating lesson plan and media learning, consultation, problem, class’ monitoring, solution and evalution.